Script for resilience analysis in energy systems: Python programming code and partial associated data of four cogeneration plants - da Silva, Fellipe Sartori [UNESP]; Matelli, José Alexandre [UNESP] (Elsevier, 2021)
This article presents a script developed to evaluate resilience in energy systems. The files corresponding to the system description, simulation and metrics calculation are included in the dataset, as well as partial raw and processed data from the associated paper [1]. The model was developed focusing on covering all cogeneration and power plants, being the user responsible for describing the system, simulating and processing the data in the files here available. In the present work, the steps for the simulation are presented in detail, which contributes to other researchers that are interested in either adopting resilience as one of the possible system analyses or understanding the processes of metrics calculation of the associated paper.
Keywords: Cogeneration; Energy system; Resilience; System design